Improvement of Counting Abilities Through the Powerpoint Media in Elementary School Grade II - Wanti, Estu Zunia (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This purpose of the study was to improve the ability to counting with long and short storage techniques with powerpoint for students grade II of SD Negeri Selomerto for the 2020/2021 academic year. This research was conducted in two cycles. Where in each cycle has stages that start from doing planning, action, observation and reflection. The results of the study : cycle 1 shows increase from pre cycle, 55% students complete and cycle two shows increase form cycle 1, 76% student complete from 29 students in the class. The results of the research that have been done show that the powerpoint media improves students counting skills, especially in adding long and short storage techniques in Grade II SD Negeri Selomerto.